Physico-chemical Properties, Mineral Matter, Organic Acid, Amino Acid, and Plant Hormones Content of Goji Berry (Lycium barbarum L.) Grown in Turkey - Rabia Talay; Ümmügülsüm Erdoğan; Metin Turan (Turkish Journal of Agriculture: Food Science and Technology)
With high nutritional value, goji berry is an important fruit for human nutrition and health. Goji berry cultivation is done widely in many countries, farming has become widespread in recent years in Turkey. In study grown goji berry (Lycium barbarum L.) in Turkey are determined the physical and chemical characteristics of fruit (pH, titration acidity, dry matter content, ash content, water activity (aw) value, protein content, HMF content, total phenolic content, total sugar content, reducing sugar content, sucrose content, colour values, mineral contents, organic acid contents, amino acid contents and some plant hormone content). Goji berry fruits have pH value 5.18, titration acidity value 2.16%, dry matter content 89.40%, ash content 4.30%, water activity (aw) value 0.35, protein content 13.18%, HMF content 9.38 mg/kg, total phenolic content 9.05 mg GAE/g, total sugar content 59.26%, decreasing sugar content 57.35%, sucrose content 1.90%, L* value 40.33, a* value 22.97, b* value 33.00, C* value 40.21, H° value 55.15. In addition, the mineral content, organic acid content, amino acid content and some plant hormones of goji berry fruits were determined by analysis.